The Influence of School Climate and Goal Achievement Structure in Nigerian Public Schools - Akinnubi, Olaolu Paul; Ajape, Rasheedat Oladunni; Adeoye, Moses Adeleke (International Journal of Universal Education, 2024)
The paper explores the importance of school climate and goal achievement structure in Nigerian public schools. It highlights the significance of these elements in shaping the educational environment. The school climate, influenced by factors such as leadership, teacher-student relationships, safety and discipline, significantly impacts student well-being, academic performance and overall school success. The goal achievement structure is also crucial in Nigerian public schools, drives academic progress and shapes the future of students. The relationship between school climate and goal achievement structure is also explored. This understanding is crucial for fostering a conducive educational environment and achieving academic objectives. The paper then delves into goal achievement structure, its significance in Nigerian public schools to firm its alignment with national education objectives and the challenges associated with its implementation. It highlights the complexities of implementing these components within the Nigerian public school system. In conclusion, understanding the influence of school climate and goal achievement structure in Nigerian public schools is crucial for improving education quality and fostering an academic and personal growth environment.